2007
DOI: 10.1007/s12041-007-0031-x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, characterization and genetic analysis of canine GATA4 gene in a family of Doberman Pinschers with an atrial septal defect

Abstract: GATA4 is expressed early in the developing heart where it plays a key role in regulating the expression of genes encoding myocardial contractile proteins. Gene mutations in the human GATA4 have been implicated in various congenital heart defects (CHD), including atrial septal defect (ASD). Although ASD is the third most common CHD in humans, it is generally rare in dogs and cats. There is also no obvious predilection for ASD in dogs and cats, based on sex or breed. However, among dogs, the incidence rate of AS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
3
1
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Therefore, cardiac transcription factors modulating the levels of genes involved in cardiomorphogenesis may be the prime target gene for the identification of the genetic aetiology(ies) for TOF or other compound congenital cardiac defects. Despite the importance of identification of genetic aetiology(ies) in dogs with CHD, those studies have rarely been performed in dogs, although several candidate genes for canine CHD have been recently isolated and investigated (Lee et al. 2007, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, cardiac transcription factors modulating the levels of genes involved in cardiomorphogenesis may be the prime target gene for the identification of the genetic aetiology(ies) for TOF or other compound congenital cardiac defects. Despite the importance of identification of genetic aetiology(ies) in dogs with CHD, those studies have rarely been performed in dogs, although several candidate genes for canine CHD have been recently isolated and investigated (Lee et al. 2007, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have suggested that the non-genetic factors such as poorly controlled maternal diabetes, maternal alcohol, drugs and cigarette consumptions during pregnancy are linked to the congenital heart disease including ASDs [28-33, 45].…”
Section: Discussionmentioning
confidence: 99%
“…This last view allows a more precise measurement of ASD-OS2 size in dogs and cats (Figure 19-39) [78]. On the left parasternal apical 4 chambers views, the very thin fossa ovalis may not be seen (echo dropout) due to the fact that the ultrasound beam is parallel to the interatrial septum.…”
Section: Bidimensional Echocardiographymentioning
confidence: 99%